Manajemen Program Akselerasi dalam Meningkatkan Mutu dan Daya Saing Madrasah - Mustajib; Lily Nur Azizah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Improving the quality and competitiveness of madrasahs is a strategic challenge amid increasingly competitive educational competition. One effort carried out by madrasahs is through the implementation of an acceleration program based on the Semester Credit System (SKS) for high-ability students. This study aims to analyze the management of the acceleration program in enhancing the quality and competitiveness of madrasahs at MTsN 1 Kediri, covering aspects of planning, implementation, evaluation, as well as the challenges and solutions of its implementation. This study uses a qualitative approach with a descriptive research type. Data collection techniques were conducted through in-depth interviews, observations, and documentation, with informants including the head of the madrasah, program managers, teachers, and students. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions, as well as testing the validity of the data using triangulation. The results of the study indicate that the management of the acceleration program at MTsN 1 Kediri is implemented systematically and continuously, marked by structured planning, adaptive learning implementation according to the characteristics of the students, and program evaluation oriented towards improving both academic and non-academic quality. The acceleration program has been proven to make a significant contribution to enhancing student achievement and strengthening the school's competitiveness at the regional level. The main challenges include managing study time and improving teacher competence, which are addressed through professional training and strengthening institutional collaboration. This research has implications for enhancing Islamic education management practices, as well as providing practical contributions as a model for managing acceleration programs that can be replicated by other madrasahs to improve the quality and competitiveness of institutions.